Cold-flo, Sila-bac, and Silo-Best for corn silage - Bolsen, K.; Ilg, H.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Four corn silages (41 to 46% DM) were made August 23 to 26, 1978; treatments were: 1) no additive (control), 2) 8.16 lbs of Cold-flo ammonia per ton, 3) 1.0 lb of Sila-bac per ton, and 4) 1.0 lb of Silo-Best per ton. Silos were opened after 139 days and each was full-fed to 15 heifer calves (3 pens of 5 calves) during a 112-day trial (January 12 to May 4, 1979). The complete-mixed rations contained 88% silage and 12% supplement (Table 19.1). Control silage was supplemented with soybean meal for one group of heifers and urea for another group (urea supplying 33% of the total ration crude protein equivalent). The Cold-flo silage was fed with a milo supplement with no additional crude protein added. Sila-bac and Silo-Best silages were supplemented with soybean meal.
Keywords: Beef; Corn silage; Soybean meal